2019
DOI: 10.1002/jcp.29202
|View full text |Cite|
|
Sign up to set email alerts
|

Retracted:Propofol exerts anticancer activity on hepatocellular carcinoma cells by raising lncRNA DGCR5

Abstract: Hepatocellular carcinoma is one of the most fatal cancers worldwide. Propofol is an intravenous anesthetic extensively used in clinical. Herein, we tested the anticancer activity of propofol on hepatocellular carcinoma, along with the internal molecular mechanism related to lncRNA DiGeorge syndrome critical region gene 5 (DGCR5).Followed by propofol stimulation, hepatocellular carcinoma Huh-7 and HepG2 cell viability, proliferation, migration, invasion, and apoptosis were tested, respectively.Then, DGCR5 expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 37 publications
1
11
0
Order By: Relevance
“…These aforementioned findings indicated that propofol may not serve an anticancer role in all types of neoplasms. The cell type, propofol concentration and duration of stimulation in the present study were consistent with those implemented in previous studies ( 37 , 38 ). There are several possible explanations for the observed differences between the current results and previous findings.…”
Section: Discussionsupporting
confidence: 91%
“…These aforementioned findings indicated that propofol may not serve an anticancer role in all types of neoplasms. The cell type, propofol concentration and duration of stimulation in the present study were consistent with those implemented in previous studies ( 37 , 38 ). There are several possible explanations for the observed differences between the current results and previous findings.…”
Section: Discussionsupporting
confidence: 91%
“…For example, Sun et al confirmed that propofol inhibited the development of hepatocellular carcinoma via increasing the level of lncRNA DGCR5. 27 Chen et al revealed that propofol reduced the level of lncRNA ANRIL to repress the proliferation and mobility of thyroid cancer cells. 28 In this study, we found that TMPO-AS1 was highly expressed in EC cells, and TMPO-AS1 expression was downregulated due to the treatment of propofol.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, LINC00460 has also been confirmed to promote the progression of multiple cancers through different target genes [32][33][34]. The last lncRNA, DGCR5, is slightly different because when it is highly expressed it exerts anticancer activity in various cancers, including gastric cancer, hepatocellular carcinoma, cervical cancer, and bladder cancer, suggesting a good prognosis [35][36][37][38]. Interestingly, DGCR5 promotes LUAD progression by inhibiting hsa-mir-22-3p [39], which means higher expression DGCR5 implies a worse prognosis for LUAD patients and this finding was consistent with our current survival analysis results.…”
Section: Discussionmentioning
confidence: 99%